Des étudiants en lettres face aux humanités numériques : une expérience pédagogique - Motasem Alrahabi; Glenn Roe; Marguerite Bordry; Camille Koskas; James Gawley (Humanités Numériques)
This paper presents an experiment in digital humanities pedagogy enacted as part of a Master course at Sorbonne Université for students of French literature and language with little to no digital research experience. For the final evaluation, students worked in groups on projects that allowed them to deploy the skills and expertise acquired during the course. Students evaluated concretely the potential benefits of digital humanities methods for their own studies, either in the form of a critical reflection on a subject related to digital approaches to literary research, or through the conception and execution of a research project using digital tools and corpora of their choosing. The authors supervised this work as tutors, providing support through the different stages of each project’s elaboration. Based on these interactions, as well as course feedback in the form of a survey, this paper presents reflections on the challenges of teaching digital humanities methods to beginners, and on the potential that these methods hold for transforming traditional university curricula.